Exploring Coal Biodesulfurization Potential of a Novel Organic Sulfur Metabolizing Rhodococcus spp. (Eu-32) – A Case Study. Issue 6 (2nd July 2016) - Akhtar, Nasrin; Ghauri, Muhammad A.; Akhtar, Kalsoom
ABSTRACT: Coal is one of the most abundant nonrenewable fossil fuels, in Pakistan. However, in general, the quality of coal is too low to offset the practical, economic, and regulatory barriers to its utilization. High sulfur content comes up as one of the bottlenecks in productive usage of indigenous coal. Biotechnology can emerge as a panacea for upgrading the huge reserves of high sulfur coal. In current study, the sulfur removal potential of Rhodococcus spp. (Eu-32) was investigated using coal from Dukki, Baluchistan, Pakistan. Biodesulfurization process was optimized for various parameters and maximum decrease of 40% and 60% in total and organic sulfur contents, respectively were achieved in 15 days. The Langmuir and Brunauer–Emmett–Teller (BET) surface areas of the biotreated coal were increased by 20 and 16 times, respectively. Scanning electron microscope showed higher tendency of attachment of bacterial cells to the coal particles. Our results revealed that Eu-32 could remove significant amounts of organic sulfur from coal and could be used in the pre-combustion operations with appropriate arrangements.